Migration tracing and kinematic state concept embedded in discrete fracture network for modeling hydrocarbon migration around unlined rock caverns - Javadi, M.; Sharifzadeh, Mostafa; Shahriar, K.; Sayadi, S. (Elsevier, 2016)
This paper presents a numerical method for the modeling of hydraulic confinement and hydrocarbon migration around the unlined rock caverns (URCs) by directly applying distinct fracture network (DFN) concept. A "migration tracing" algorithm for the assessment of hydrocarbon migration around URCs was developed based on the applying migration cessation criterion and pathway analysis in the DFN realizations. The veracity of the developed numerical method was explored by predicting the hydrocarbon migration in a uniform fracture network around an unlined cavern that consists with results obtained from the finite element continuum fluid flow analysis. Finally, the applicability of the proposed method was evaluated by simulation of hydrocarbon migration in the DFN realizations around a URC. The results demonstrate that the hydrocarbon migration is sensitive to the hydraulic boundary conditions, and the geometrical properties of fractures. Establishing sufficient water pressure in the fracture system controls hydrocarbon migration; however, the effect of external water pressure on the hydrocarbon migration is controlled by the fractures geometry. Consequently, local migration paths may develop around storage caverns through the intricately connected fracture network, despite the presence of high pressurized water curtain. The proposed method may prove useful for better design analysis of hydraulic confinement around URCs, or inclusions in simulators for computational demands.